Key Factors of Email Subject Generation - Xue, Mingfeng; Zhang, Hang; Lv, Jiancheng (Neural Information Processing, 2020)
Automatic email subject generation is of great significance to both the recipient and the email system. The method of using deep neural network to solve the automatically generated task of email subject line has been proposed recently. We experimentally explored the performance impact of multiple elements in this task. These experimental results will provide some guiding significance for the future research of this task. As far as we know, this is the first work to study and analyze the effects of related elements.